2021
DOI: 10.1177/20552173211061550
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and safety of three times weekly dosing regimen of glatiramer acetate in relapsing multiple sclerosis patients: Seven-year results of the Glatiramer Acetate Low-frequency Administration (GALA) open-label extension study

Abstract: Objective Describe the long-term outcomes of early-start (ES) and delayed-start (DS) glatiramer acetate 40 mg/mL treatment three times weekly (GA40) for up to seven years in the Glatiramer Acetate Low-frequency Administration (GALA) study in patients with relapsing multiple sclerosis (RMS). Methods Patients were evaluated every three to six months. The primary efficacy endpoint was annualized relapse rate (ARR); additional endpoints were exploratory or post hoc. For efficacy, data from the entire exposure peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Clinical data from the European, American, and Canadian trials indicate that Copaxone® is an effective therapeutic that can decrease the frequency of MS relapse (Comi et al, 2001;Ford et al, 2010). Copaxone is injected subcutaneously along with the inactive ingredient mannitol that acts as a vehicle (Corominas et al, 2014;Rieckmann et al, 2021).…”
Section: Glatiramer Acetate (Ie Copaxone®)mentioning
confidence: 99%
“…Clinical data from the European, American, and Canadian trials indicate that Copaxone® is an effective therapeutic that can decrease the frequency of MS relapse (Comi et al, 2001;Ford et al, 2010). Copaxone is injected subcutaneously along with the inactive ingredient mannitol that acts as a vehicle (Corominas et al, 2014;Rieckmann et al, 2021).…”
Section: Glatiramer Acetate (Ie Copaxone®)mentioning
confidence: 99%
“…Long-term outcomes for up to seven years for relapsing MS patients enrolled in the Glatiramer Acetate Low-frequency Administration (GALA) study demonstrated a 0.26 adjusted annualized relapse rate in the early-start GA group (randomized to GA in the placebo-controlled trial) compared to 0.31 in the delayed start GA group (switched to GA in the open label phase), with a risk ratio of 0.83 (95% CI 0.70-0.99, p = 0.04) with no differences between the two groups in terms of EDSS (expanded disability status scale) progression (36). The longterm safety profile was similar to those reported in the clinical trials, with the most common being injection site reactions (40%) and immediate post-injection reactions (12%); 11% patients had serious adverse events with 4 deaths that were deemed not related to the treatment drug (36).…”
Section: Glatiramer Acetatementioning
confidence: 95%
“…Clinical trials of patients with RRMS have revealed comparable reductions in ARR for IFNs, glatiramer acetate, and teriflunomide and largely similar effects on time to first relapse for IFNs and glatiramer acetate (Table 1 ) [ 40 , 43 46 , 57 , 58 ]. Both teriflunomide and IFN therapy have been reported to delay disability progression [ 43 , 46 , 59 , 60 ], whereas glatiramer acetate appears to have no significant impact other than a potential stabilizing effect of long-term disability progression in patients with mild disease activity [ 45 , 53 ].…”
Section: Existing Treatment Paradigmsmentioning
confidence: 99%